Changes in medical treatment and surgery rates in inflammatory bowel disease: a nationwide cohort study 1979–2011. Issue 10 (20th September 2013) - Rungoe, Christine; Langholz, Ebbe; Andersson, Mikael; Basit, Saima; Nielsen, Nete M; Wohlfahrt, Jan; Jess, Tine
Abstract : Introduction: Treatment possibilities have changed in inflammatory bowel disease (IBD). We assessed changes in medical treatment and surgery over time and impact of medications on risk of surgery in a population-based cohort. Methods: 48 967 individuals were diagnosed with IBD (Crohn's disease (CD), 13 185; ulcerative colitis (UC), 35 782) during 1979–2011. Cumulative probability of receiving 5-aminosalicylic acids (5-ASA), topical, oral corticosteroids, thiopurines, and tumour necrosis factor-α (TNF-α) blockers, and of first minor or major surgery according to period of diagnosis, was estimated. Medication use and risk of surgery was examined by Cox regression. Results: 5-year cumulative probability of first major surgery decreased from 44.7% in cohort (1979–1986) to 19.6% in cohort (2003–2011) (p < 0.001) for CD, and from 11.7% in cohort (1979–1986) to 7.5% in cohort (2003–2011) (p < 0.001) for UC. Minor surgery risk decreased significantly in CD. From cohort (1995–2002) to cohort (2003–2011), a significant increase in use of thiopurines and TNF-α blockers was observed, paralleled by a significant decrease in use of 5-ASA and corticosteroids. Comparing use of azathioprine (or oral corticosteroids) to never-use, no convincing surgery-sparing effect was found. Comparing use in 3+ months of a given drug with use <3 months, only 3+ months use of oral corticosteroids reduced the risk of surgery in patients with disease duration of >1 year. Conclusions: Parallel to an increasing use of thiopurines and TNF-α blockers in IBD over time, a persistent significant decrease in surgery rates was observed along with a significant decrease in use of 5-ASA and corticosteroids. However, no convincing surgery-sparing effect of newer medications was found.